THE GALLERY SPACE – THE HOME OF PAINTING - Dimitrova, Denitsa (E-Journal VFU, 2026)
The home of the painting protects the dreamer and allows him to dream in peace. The gallery space, the picturesque "home," as a home of art, shelters the soul of the artist; it is the topos of the creative person in the world, not just a place with some vertical or horizontal perspective and angles.
Keywords: loneliness; afterlife; spirit; soul